Financial development and economic growth nexus in SSA economies: The moderating role of telecommunication development - Mac Junior Abeka; Eric Andoh; John Gartchie Gatsi; Seyram Kawor (Cogent Economics & Finance, 2021)
The economic growth of most sub-Saharan African countries in the past years has not been able to equalize with other regions. Even though financial development has been highlighted in several empirical literature as a factor that could spur up economic growth, the level of financial development in sub-Saharan Africa is not effectively channeled into desired levels of economic growth. However, there is an indication in the literature that financial development will be more relevant to the economic growth of sub-Saharan African economies that have strong telecommunication infrastructure. Using the system General Method of Moment estimation technique, the paper found that telecommunication infrastructure enhances the effect of financial development on the economic growth of sub-Saharan African economies. It is therefore recommended that sub-Saharan African economies should apply appropriate measures to boost their telecommunication infrastructure so that gains from the financial sector can effectively be channeled into economic growth.
Keywords: 330; economic growth; financial development; sub-Saharan Africa; telecommunication infrastructure